Pembelajaran Hal Yang Harus Dilakukan Oleh Orang Tua Dengan Anak Berkebutuhan Khusus - Mawaddah, Wafa’; Yasmin, Najwa Khalisa (UNITY: Journal of Community Service, 2024)
The birth of a child is a highly anticipated moment for every married couple, with hopes that the newborn will be perfect both physically and mentally. However, the reality can be different when a child is diagnosed with developmental disorders. Parents of children with special needs (ABK) play a crucial role in the upbringing and development of their child, as parental involvement can significantly influence the child's physical, psychological, intellectual, emotional, and social growth. This service program aims to provide education to parents of children with special needs through the distribution of brochures at RSUD Sultan Suriansyah Banjarmasin. The activity was conducted on June 20, 2024, by researchers from the Islamic Psychology Program at UIN Antasari Banjarmasin. The results show that this educational effort was well received by the parents, who gained a deeper understanding of the importance of their role in supporting their child's development. This education is expected to enhance parents' knowledge of activities they can engage in to help their children with special needs grow and develop effectively.